2018
DOI: 10.1002/jcp.26512
|View full text |Cite
|
Sign up to set email alerts
|

Contractile heterogeneity in ventricular myocardium

Abstract: The transmural heterogeneity of the contractility in ventricular muscle has not been well-studied. Here, we investigated the calcium transient and sarcomere contraction/relaxation in the endocardial (Endo) and epicardial (Epi) myocytes. Endo and Epi myocytes were isolated from C57/BL6 mice by Langendorff perfusion. Ca transient and sarcomere contraction/relaxation were recorded simultaneously at different stimulation frequencies using a dual excitation fluorescence photomultiplier system. We found that the End… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…Consistent with findings on mouse unloaded single-cell shortening (Kondo et al, 2006;Pan et al, 2018), our data showed that the amplitude of auxotonic tension was higher and T max was greater in single Endo cells compared with Epi ones. The Endo and Epi mathematical models that we developed for the study reproduced the experimental data on transmural differences in contraction and literature data on the transmural gradient in AP and Ca 2+ parameters ( Table 2).…”
Section: The Transmural Gradient In Myocyte Morphology and Contractilsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with findings on mouse unloaded single-cell shortening (Kondo et al, 2006;Pan et al, 2018), our data showed that the amplitude of auxotonic tension was higher and T max was greater in single Endo cells compared with Epi ones. The Endo and Epi mathematical models that we developed for the study reproduced the experimental data on transmural differences in contraction and literature data on the transmural gradient in AP and Ca 2+ parameters ( Table 2).…”
Section: The Transmural Gradient In Myocyte Morphology and Contractilsupporting
confidence: 92%
“…Endo cardiomyocytes also showed a slower Ca 2+ transient. Consistently with literature data (Dilly et al, 2006;Rossow et al, 2006;Pan et al, 2018), the Endo model had a higher Ca 2+ transient amplitude (15% relative to the Endo model) and a higher diastolic Ca 2+ level (12% relative to the Epi model) compared with the Epi model ( Table 2).…”
Section: Cell Morphologysupporting
confidence: 90%
See 1 more Smart Citation
“…Many researchers have attempted to demonstrate the causal role of ER–mitochondrial microdomain in modifying I/R-mediated cell death. First, it is well documented that the sensitivity of cardiomyocyte to death (regardless of apoptosis and necroptosis) is fine-tuned by cellular calcium concentration ( Mofid et al, 2017 ; Zhu et al, 2017 ; Pan et al, 2018 ) which drastically is affected by the ER–mitochondrial microdomain. Based on previous studies ( Zhou et al, 2018d ; Zhu H. et al, 2018 ), IP3R expression is upregulated in response to I/R stress, leading to the calcium overload in mitochondria.…”
Section: Apoptosis and Necroptosismentioning
confidence: 99%
“…The averaged SL at end-systole was ∼9% smaller than at end-diastole. The amount of SL shortening is slightly lower compared to the data obtained in mouse cardiomyocytes in vivo under a natural beat frequency ( Kobirumaki-Shimozawa et al, 2016 ), but is of the same magnitude or even higher compared to the averaged fractional shortening of isolated rat and guinea-pig LV cardiomyocytes, which were mechanically unloaded and paced at a relatively low rate ( Natali et al, 2002 ; Wan et al, 2003 ; Carneiro-Júnior et al, 2013 ; Chung and Campbell 2013 ; Pan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 58%